THE EFFECT OF MONETARY POLICY ON MICRO, SMALL AND MEDIUM ECONOMIC GROWTH - Robert Fransiska; Lite, Sri Hartini (Adisam Publisher, 2024)
The effect of monetary policy on the economic growth of Micro, Small and Medium Enterprises (MSMEs) can be defined as the impact that policies implemented by the central bank, particularly those relating to interest rates and money supply, have on the operating conditions and growth capabilities of MSMEs. Monetary policy plays a role in determining borrowing costs and inflation rates, which directly affect the capacity of MSMEs to access funds, make investments, and manage their business costs and product selling prices. The study conducted in this research uses the literature research method. The results show that the provision of low interest rates and controlled inflation create favourable conditions that facilitate MSMEs to expand their businesses and make investments. Price stability resulting from sound monetary policy maintains or increases consumer purchasing power, benefiting the sales and service sectors of MSMEs. However, variable currency exchange rates and limited access to credit sources pose challenges that limit the full impact of monetary policy on MSMEs, especially in the case of unexpected policy changes that could destabilise MSME operations.